2022
DOI: 10.3389/fnmol.2022.881954
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Intracranial Arteries in Adult Patients With Moyamoya Disease Reveals Novel Insights Into Its Pathogenesis

Abstract: Moyamoya disease (MMD) is a rare, progressively steno-occlusive cerebrovascular disorder of unknown etiology. Here, we revealed the gene expression profile of the intracranial arteries in MMD via the RNA-sequencing (RNA-seq). We identified 556 differentially expressed genes (DEGs) for MMD, including 449 and 107 significantly upregulated or downregulated genes. Compared with atherosclerosis-associated intracranial artery stenosis/occlusion (AS-ICASO) controls, upregulated genes were mainly involved in extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…More studies using intracranial vessel samples should be delivered in the future. 64 In the follow-up studies, continuous investigations into genetic, angiogenic, and inflammatory factors will contribute to a deeper understanding of the etiology and pathogenesis of MMD and provide novel and effective inchoate diagnostic and therapeutic targets for MMD. This might ultimately be conducive to delaying or reversing the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More studies using intracranial vessel samples should be delivered in the future. 64 In the follow-up studies, continuous investigations into genetic, angiogenic, and inflammatory factors will contribute to a deeper understanding of the etiology and pathogenesis of MMD and provide novel and effective inchoate diagnostic and therapeutic targets for MMD. This might ultimately be conducive to delaying or reversing the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our previous work has found that patients with MMD exhibited significantly higher expression of MMP-2 and TIMP-1 in MCA specimens. 64 MMPs were elevated after RNF213 silencing in ECs, indicating that RNF213 negatively controls the expressions of MMPs. 65 These results suggested that the disrupted balance between MMPs and TIMPs may be involved in the MMD pathophysiology through regulating ECM.…”
Section: Matrix Metalloproteinases and Tissue Inhibitor Of Metallopro...mentioning
confidence: 96%
See 1 more Smart Citation
“…The importance of sex differences in MMA are also reported in a transcriptomic profiling of ICA in adult patients. The study identified 133 and 439 sex-specific differentially expressed genes (DEGs) for men and women through an RNA sequencing (RNAseq) analysis [ 44 ]. Another RNAseq study identified a total of 533 DEGs in the peripheral blood of MMA patients, further highlighting the importance of a transcriptomic approach in a multifactorial disease [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase 9 (MMP-9) has an important role in extracellular matrix remodeling and angiogenesis regulation, and it is the main enzyme in the degradation of extracellular matrix proteins. It has been already reported as an important factor in MMA [ 42 , 43 , 44 , 45 ]. Interleukin 6 (IL-6) is a soluble mediator with a pleiotropic effect on inflammation, immune response, and hematopoiesis [ 46 ].…”
Section: Introductionmentioning
confidence: 99%